Predicting Current-Induced Drag in Emergent and Submerged Aquatic Vegetation Canopies - van Rooijen, Arnold; Lowe, Ryan; Ghisalberti, Marco; Conde-Frias, Mario; Tan, Liming (Frontiers in Marine Science, 2018)
Canopies formed by aquatic vegetation, such as mangroves, seagrass and kelp, play a crucial role in altering the local hydrodynamics in rivers, estuaries and coastal regions, and thereby influence a range of morphodynamic and biophysical processes. Prediction of the influence of canopies on these hydrodynamic processes requires a fundamental understanding of canopy drag, which varies significantly with both flow conditions and canopy properties (such as density and submergence). Although our knowledge on canopy drag has increased significantly in recent decades, a conclusive, physics-based description for canopy drag that can be applied to both emergent and submerged canopies is currently lacking. Here, we extend a new theoretical canopy drag model (that employs the velocity between canopy elements as the reference velocity) to submerged aquatic canopies. The model is validated for the first time with direct measurements of drag forces exerted by canopies across broad ranges of flow conditions and canopy density and submergence. The skill and broader applicability of the model are further assessed using a comprehensive set of existing experimental data, covering a broad range of natural conditions (including flexible vegetation). The resulting model provides a simple tool to estimate canopy drag forces, which govern hydraulic resistance, sediment transport and biophysical processes within aquatic ecosystems.